Inovasi Pertanian Modern Dalam Strategi Pemasaran Hasil Pertanian KWT Sumur Mangga Dengan Aplikasi Sayurbox - Daz Vholasky Anggraini; Ahmad Jurnaidi Wahidin; Miftah Faroq Santoso; Yusuf Unggul Budiman (Jurnal Informasi Pengabdian Masyarakat, 2024)
Women's empowerment in agriculture is a key aspect of rural development in various countries, including Indonesia. Women Farmer Groups (WFGs) are one effective form of empowerment in enhancing the capacity and economic independence of women farmers. In Jl. Sumur Mangga I, Gaga, Larangan District, Tangerang City, WFG Sumur Mangga is an interesting example of how women farmers are able to transform unproductive land into fertile and productive fields in response to the COVID-19 pandemic and the need for food security. Through the One-Day Training (ODT) method, this community service activity was conducted with a focus on providing training in modern agricultural technology and marketing strategies to members of WFG Sumur Mangga. The results showed a high level of satisfaction, with an average score of 4.45 out of 5, indicating a very positive response from the participants. The theoretical discussion highlights the importance of gender roles in rural and agricultural development, while the practical findings of WFG Sumur Mangga illustrate successful collaboration between the local community and academic institutions in achieving sustainable development goals. The conclusion confirms that this community service activity has had a significant positive impact and has met the participants' expectations, thus making a meaningful contribution to community development in the area.